The Hidden Moral Message in the Hyperreality of the Novel 'Al-Bintū Allatī Lā Tuhibbu Ismahā' - Nur Illiyyin Setya Mufti; M Anwar Masadi; Fika Burhan Tajalla (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2023)
This research aims to discover various moral messages within the series of hyperreality situations in the novel "Al-Bintū Allatī Lā Tuhibbu Ismahā" by Alīf Syāfāk. Hyperreality is a theory that deals with various states that are exaggerated compared to reality. Hyperreality is accompanied by various simulations. This theory was proposed by a French philosopher Jean Baudrillard. This concept is closely tied to the postmodern era and technological advancements in the age of globalization. This study is a qualitative descriptive research that describes all the findings of its data. In this research, 8 depictions of hyperreality were found, namely: 1) Zahrah Sārdūniyā: A Strange Name, 2) Belief in the Myth of Space Twins, 3) Imaginative Polar Bear, 4) The Strangeness of the Magical Globe, 5) New Friend from the Eighth Continent, 6) Winged Horses, 7) Fantasy Forest, and 8) Impressive Journey Experience. Additionally, 3 moral messages were also discovered, which are: 1) Self-love, 2) Thinking Before Acting, and 3) Don't Give Up Before Trying.